Impact of CYP2E1, GSTA1 and GSTP1 gene variants on serum alpha glutathione S-transferase level in patients undergoing anaesthesia. Issue 1 (December 2016) - Mikstacki, Adam; Skrzypczak-Zielinska, Marzena; Zakerska-Banaszak, Oliwia; Tamowicz, Barbara; Skibinska, Maria; Molinska-Glura, Marta; Szalata, Marlena; Slomski, Ryszard
Abstract Background The serum glutathione S-transferase alpha (α-GST) concentration has been used as a marker of hepatic condition. After sevoflurane anaesthesia a mild impairment of hepatocellular integrity was observed. Genetic polymorphisms inCYP2E1, GSTA1 andGSTP1 genes, affecting enzymes activity, may possibly influence the hepatotoxic effect of sevoflurane. The aim of this study was to assess the influence of genetic polymorphism ofCYP2E1, GSTA1 andGSTP1 genes on serum α-GST level in 86 unrelated patients representing ASA physical status I-II, undergoing laryngological surgery under general anaesthesia with sevoflurane. Methods The serum samples from three perioperative time points were analyzed using ELISA. Genetic variants were detected by pyrosequencing and sequencing. Finally, the statistical associations between serum α-GST concentration and analyzed alleles ofCYP2E1, GSTP1 andGSTA1 genes were estimated. Results The alleleGSTA1*B (−567G, −69T, −52A) frequency was 0.43, whereas the alleles c.313G and c.341T ofGSTP1 were identified with frequencies of 0.28 and 0.1 respectively. The -1053T allele of theCYP2E1 gene was observed with 0.01 frequency. We found serum α-GST concentrations in homozygous changes c.313A>G and c.341C>T of theGSTP1 gene significantly higher at the end of anaesthesia as compared with the levels at pre-anaesthetic and 24 h post-anaesthetic time points. Moreover, GSTA1 wild type genotype was associated with increased α-GST concentration at 24 h after the end of anaesthesia. Conclusions GSTP1 gene polymorphism has an impact on the perioperative serum α-GST concentration in patients undergoing sevoflurane anaesthesia. A similar association, although not statistically significant exists betweenGSTA1 gene variants and perioperative serum α-GST level.